1985
DOI: 10.1203/00006450-198510000-00074
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Minor Congenital Anomalies in Diabetic Children

Abstract: With the discovery of hpGRF and hCRF pituitary function can be assessed by the use of four physiologic releasing hormones. After a rest of two hours to reach basal cortisol levels, healthy young male volunteers received a bolus of the following releasing hormones: 1) GRF (100 119) + CRF (50 09) + TRH ( 2 W pg) + LIWI (1Wug) 2) GRF + TRH 3) CRF + TRH 4) LHRH + TRH 5) each releasing hormone alone (n=5 in each group). During the following two hours, GH, ACTH, cortisol, TSH, LH, FSH and prolactin were measured eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the past three decades, numerous studies reported the incidence of minor physical anomalies in a variety of disorders: diabetes [Méhes et al, 1986], metabolic diseases [Méhes, 1991], isolated urinary tract malformations [Méhes and Pinter, 1990], mental retardation [Smith and Bostian, 1964; Firestone et al, 1978; Meggyessy et al, 1980; Van Karnebeek et al, 2002a], cerebral palsy [Miller, 1989; Coorssen et al, 1991], hyperactivity [Waldrop and Goering, 1971; Quinn and Rapoport, 1974; Firestone et al, 1978], autism [Links et al, 1980; Accardo et al, 1991; Miles and Hillman, 2000; Van Karnebeek et al, 2002b], and schizophrenia and mood disorders [Gualtieri et al, 1982; Guy et al, 1983; Green et al, 1989, 1994a,b; Lohr and Flynn, 1993; Alexander et al, 1994; O'Callaghan et al, 1995; Lane et al, 1997; Trixler et al, 1997; Griffiths et al, 1998; Ismail et al, 1998, 2000; Lawrie et al, 2001; Trixler et al, 2001; Scutt et al, 2001; McGrath et al, 2002]. A few studies deserve more attention here.…”
Section: Discussionmentioning
confidence: 99%
“…In the past three decades, numerous studies reported the incidence of minor physical anomalies in a variety of disorders: diabetes [Méhes et al, 1986], metabolic diseases [Méhes, 1991], isolated urinary tract malformations [Méhes and Pinter, 1990], mental retardation [Smith and Bostian, 1964; Firestone et al, 1978; Meggyessy et al, 1980; Van Karnebeek et al, 2002a], cerebral palsy [Miller, 1989; Coorssen et al, 1991], hyperactivity [Waldrop and Goering, 1971; Quinn and Rapoport, 1974; Firestone et al, 1978], autism [Links et al, 1980; Accardo et al, 1991; Miles and Hillman, 2000; Van Karnebeek et al, 2002b], and schizophrenia and mood disorders [Gualtieri et al, 1982; Guy et al, 1983; Green et al, 1989, 1994a,b; Lohr and Flynn, 1993; Alexander et al, 1994; O'Callaghan et al, 1995; Lane et al, 1997; Trixler et al, 1997; Griffiths et al, 1998; Ismail et al, 1998, 2000; Lawrie et al, 2001; Trixler et al, 2001; Scutt et al, 2001; McGrath et al, 2002]. A few studies deserve more attention here.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of minor physical anomalies has also been studied in search of relationships between various non‐syndromic disorders and abnormal embryogenesis or phenogenesis. Well‐known examples are the studies in childhood cancer [Kobayashi et al, 1968; Stojimirovic, 1981; Méhes et al, 1985, 1994, 1998; Fékété et al, 1987; Roganovic et al, 2002; Merks et al, 2003], diabetes mellitus [Méhes et al, 1986], metabolic disorders [Méhes, 1991], isolated urinary tract malformations [Méhes and Pinter, 1990], mental retardation [Smith and Bostian, 1964; Firestone et al, 1978; Meggyessy et al, 1980; Coorssen et al, 1991; Ulovec et al, 2004; Van Karnebeek et al, 2005], cerebral palsy [Miller, 1989], hyperactivity [Waldrop et al, 1968, 1978; Waldrop and Goering, 1971; Quinn and Rapoport, 1974; Walker, 1977; Campbell et al, 1978; Firestone et al, 1978; Burg et al, 1980; Links, 1980; Links et al, 1980; Simonds and Aston, 1981; Gualtieri et al, 1982; Vanoverloop et al, 1982; Fogel et al, 1985; Accardo et al, 1991], autism [Steg and Rapoport, 1975; Rodier et al, 1997; Miles and Hillman, 2000; Van Karnebeek et al, 2002], and other psychiatric disorders [Steg and Rapoport, 1975; Guy et al, 1983; Green et al, 1987, 1989, 1994a,b; O'Callaghan et al, 1991, 1995; McNeil et al, 1992; Lohr and Flynn, 1993; Alexander et al, 1994; McGrath et al, 1995, 2002; Lane et al, 1997; Lohr et al, 1997; Trixler et al, 1997, 2001; Akabaliev and Sivkov, 1998; Griffiths et al, 1998; Ismail et al, 1998, 2000; Weinstein et al, 1999; Akabaliev et al, 2001; Lawrie et al, 2001; Scutt et al, 2001; Schiffman et al, 2002; Elizarraras‐Rivas et al,…”
Section: Introductionmentioning
confidence: 99%
“…Dysmorphic features not only are found in children with well‐defined clinical syndromes, but also often occur in the general population . They are related to an increased incidence of cancer, diabetes mellitus, autism, and schizophrenia . These associations indicate that dysmorphic features may be used as indicators of abnormal embryonic differentiation …”
mentioning
confidence: 99%